Health Social Workers in Promoting Mental Health Equity: Voice and Agency for the Marginalized - Chandramathi Ramaswamy; R Revanth; R Jagadeesh; Tamilarasu Sampath; F. X. Lovelina Little Flower (Social Work and Society)
Globally, 1 in 4 persons have mental health issues at some point in life. However, the mental health services are not easily available, accessible and affordable to all strata of the society with varying socio-economic and cultural backgrounds. In healthcare settings, social workers work in a context where a greater number of other professionals often have medical expertise rather than social science background which makes their job unique. Thus, health social workers have a crucial role in attaining health equity at mental health settings. This article primarily investigates the contemporary role of health social workers in pioneer mental health institutions of India. The study has two phases, the first phase adopts in-depth interview method with mental health social work practitioners using self-structured interview guide that highlights the role of health social workers, especially in establishing mental health equity by de-stigmatization, reducing the disparities, equal access, etc. Totally eight Health Social Workers participated in the study from, NIMHANS, JIPMER, Vazhikatti, and National Health Mission (Coimbatore), two from each institute respectively. Thematic analysis was performed and themes were generated from the qualitative data gathered. In the second phase, literatures were identified from SCOPUS, Google Scholar and Web of Science databases for mapping pertinent literatures on international health social workers in mental health settings. The results of the thematic analysis and the literatures from various sources were compiled to understand the aspects of health social workers in addressing marginalized identity, structural inequalities, cultural sensitivity, intersectionality and providing voice and agency to the marginalized in shaping the mental health policy and programs. Therefore, the article aims to identify and bridge the gaps in the roles of health social workers in attaining health equity within this context.